PENGOLAHAN JERAMI PADI MENJADI BIOCHAR PEMBENAH TANAH UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN PADA KELOMPOK TANI DIAT I, BOLAANG MONGONDOW - Jannah, Miftahul; Mustapa, Mustapa; Hasmiati, Hasmiati; Pieter, Nathaniel Dave Emmanuel; Mandias, Praisy (Universitas Mataram, 2025)
The abundant agricultural waste in agricultural areas is generally not optimally utilized and tends to be burned, resulting in environmental pollution and the loss of potential organic matter. The Diat I Farmers Group is one of the farmer groups facing this problem, where post-harvest rice straw is not processed and soil fertility is decreasing due to dependence on chemical fertilizers. This Community Service (PKM) activity aims to improve farmers' knowledge and skills in processing rice straw into biochar as a soil conditioner. The target partners for this activity are 15 Diat I Farmers Groups. The activity method is carried out through three main stages: problem identification through observation and interviews with farmers, solution design through appropriate technology training, and technical implementation in the field. This activity produces rice straw biochar produced using a simple kon-tiki tube pyrolysis tool. Overall, there was a 51% increase in participants' understanding and skills regarding biochar materials, their benefits, and how to make it.